Literature Analysis on Prospective Teacher Students' Perceptions of the Implementation of Project Assignments in Mathematics Learning Based on Project Based Learning - Nurfaida Tasni; Hamzah Upu; Muhammad Shoaib Khan Pathan; Sherif Ismail; Andi Asrifan (Sriwijaya University Learning and Education International Journal, 2025)
This study aims to analyze prospective teacher students’ perceptions of implementing project assignments in mathematics learning based on Project-Based Learning (PBL). The study employs a qualitative descriptive literature review approach by collecting data from various secondary sources, including journals, books, conference proceedings, and relevant scientific articles. The analysis focuses on identifying key themes related to students’ perceptions, the benefits of PBL, challenges in implementation, and factors influencing the effectiveness of project assignments in mathematics learning. The findings reveal that most prospective teacher students perceive PBL positively because it enhances critical thinking, problem-solving skills, creativity, collaboration, communication, and active participation in the learning process. In addition, PBL helps students connect mathematical concepts with real-life situations, making learning more meaningful and contextual. However, several challenges remain, such as limited time, inadequate learning resources, and varying levels of student readiness. These findings are expected to contribute to curriculum development and teacher education programs supporting effective PBL implementation in mathematics education.